Andrew Gaedtke, Modernism and the Machinery of Madness: Psychosis, Technology, and Narrative Worlds (Cambridge: Cambridge University Press, 2017), 254 pp., ISBN: 9781108418003. 105 (hardcover). Issue 2 (2021) - Schiff, Noam
No abstract available